Retinal hemangioblastoma in a patient with Von Hippel-Lindau disease: A case report and literature review - Huang, Yikeng; Hu, Weiwen; Huang, Xionggao (Frontiers in Oncology, 2022)
Abstract Background: Retinal hemangioblastoma（RH）is a rare benign tumor and a considerable number of which are caused by Von Hippel-Lindau disease (VHL). As a rare autosomal-dominant inherited tumor syndrome, VHL has various clinical manifestations including RH, central nervous system hemangioblastoma, renal cell carcinoma, phaeochromocytoma and pancreatic cysts etc. Herein, we described a case of VHL-associated RH with retinal detachment who underwent both laser photocoagulation and vitreoretinal surgery and received satisfactory visual recovery. In addition, we reviewed the current diagnosis, genotype-phenotype association, and treatment of VHL-associated RH. Case description: A 34-year-old woman presented with vision loss in the right eye at our hospital. Fundus photography and angiography showed retinal detachment and multiple large hemangiomas in the right eye. The visual acuity improved significantly after laser photocoagulation and vitreoretinal surgery. Genetic analyses showed a p.Asn78Ser (c.233AG) heterozygous missense mutation in the VHL gene. Conclusion: We described a rare case of VHL-associated RH and may provide a new perspective towards ophthalmic diagnosis and treatment of this disease. RH is one of the most common manifestations of VHL and poses a serious threat to vision. Ophthalmic examination methods include fundus examination and fundus photography, etc. The management of the disease emphasizes timely follow-up, early detection of the lesion, and the decision of treatment options according to the size, location and complications of the lesion, including ablation therapy and vitreoretinal surgery. Ophthalmologists should strengthen the understanding of this rare disease for early detection and treatment of its serious effects on vison.